Dynastic change
1 online resource.
Keywords: “Dynastic Change: Legitimacy and Gender in Medieval and Early Modern Monarchy examines the strategies for change and legitimacy in monarchies in the medieval and early modern eras. Taking a broadly comparative approach, Dynastic Change explores the mechanisms employed as well as theoretical and practical approaches to monarchical legitimisation. Bringing together gender, monarchy and dynasticism, and broad in both geographical and chronological scope, the book highlights parallels across time and place, encouraging a new approach to monarchy studies. It is the perfect collection for students and researchers of medieval and early modern monarchy and gender“ --